Aqueous Dispersions of Esterified Lignin Particles for Hydrophobic Coatings - Hua, Qi; Liu, Li-Yang; Karaaslan, Muzaffer A; Renneckar, Scott (Frontiers in Chemistry, 2019)
An aqueous biopolymer dispersion for a coating material was synthesized utilizing softwood kraft lignin and a natural organic acid. The chemical treatment of lignin was a two-step process, which consisted of hydroxyethylation of the phenolics utilizing ethylene carbonate and alkaline catalyst, creating uniform aliphatic hydroxyl functionality. This procedure was followed by direct esterification of the hydroxyls with oleic acid. 13C NMR analysis of the lignin indicated 88-89% substitution of the lignin hydroxyl groups forming an ethyl oleate lignin derivative. Solutions of lignin derivatives were slowly precipitated through dialysis resulting in the modified lignin forming a stable dispersion of microparticles in distilled water. Dynamic light scattering revealed the wax-like particles had a 1-2 m average diameter. Lignin-based particles were sprayed onto a variety of surfaces to measure the ability to change the surface wettability. The lignin-based particles enhanced the hydrophobicity of all the substrates tested, increasing the contact angle for pulp sheets and solid wood. Because of the benign reagents involved in the coating synthesis, the avoidance of volatile organic solvents in the application, this process provided a low environmental solution for synthesis of hydrophobic coatings utilizing natural compounds that are known to repel water in nature.